Pendidikan Sosial dalam Perspektif ‘Abdullah Nashih ‘Ulwan (1928-1987 M.) (Studi Terhadap Kitab Tarbiyah al-Aulad fi al-Islam) - Zaini Anwar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This paper discusses the thought of ‘Abdullah Nashih‘ Ulwan (1928-1987 M.) about social education for children in his work Tarbiyah al-Aulad fi al-Islam, which focuses on methods in educating children and aspects of psychological change for adolescents. This paper explores the ideas of ‘Ulwan as outlined in his work specifically, using the content analysis method, in which the sentences of ‘Ulwan are analyzed one by one, so that the concept of planting social education for children is found. This discussion discovers four methods of Islamic social education in the perspective of ‘Abdullah Nāshih‘ Ulwān, which is to instill noble psychological principles, preserve the rights of others, maintain social ethics in general and social supervision and criticism. The application of these methods must consider aspects of changes in adolescent psychology, namely cognitive aspects, emotional aspects, moral aspects, social aspects, and aspects of religiosity.